2014
DOI: 10.1186/1129-2377-15-87
|View full text |Cite
|
Sign up to set email alerts
|

Features of migraine aura in teenagers

Abstract: BackgroundComplex migraine aura in teenagers can be complicated to diagnose. The aim of this study was to present detailed features of migraine aura in teenage migraineurs.MethodsThis cross-sectional study was conducted in the period from 2008 till 2013. A total number of 40 teenage migraineurs (20 females and 20 males) met criteria for this study. The patients were interviewed using a specially designed questionnaire for collecting data about migraine aura features. Main outcome measures were frequency of vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
(36 reference statements)
0
24
0
Order By: Relevance
“…It is also listed as the sixth highest specific cause of disability in adults 34 . Worldwide prevalence of migraine in children and adolescents was estimated to be between 7% and 11% 35 . Earlier studies have revealed central stimulus processing defects in people with migraine (with and without aura), manifesting as an interictal lack of habituation for acoustic, somatosensory, nocioceptive and visual stimuli 36 .…”
Section: Migrainementioning
confidence: 99%
“…It is also listed as the sixth highest specific cause of disability in adults 34 . Worldwide prevalence of migraine in children and adolescents was estimated to be between 7% and 11% 35 . Earlier studies have revealed central stimulus processing defects in people with migraine (with and without aura), manifesting as an interictal lack of habituation for acoustic, somatosensory, nocioceptive and visual stimuli 36 .…”
Section: Migrainementioning
confidence: 99%
“…However, this does not show whether the changes in structure and connectivity are due to repeated exposure to pain in the form of headache, if the migraine patient is more susceptible to pain, or if the structural differences themselves are the causes of the migraine disorder. Petrusic et al, (2014) showed that teenagers with migraine commonly report both visual and somatosensory symptoms during migraine aura (all reported visual symptoms, 60% reported somatosensory). Teenagers with migraine are unlikely to have had the disorder for long enough for them to develop secondary problems from the disorder, and so it seems that the visual and somatosensory symptoms might be an inherent part of the disorder itself.…”
Section: Somatosensory Integration: Pain and The Other Sensesmentioning
confidence: 99%
“…The presence of visual aura and rarely cutaneous sensation, also known as typical or conventional aura, characterizes migraine with aura. The type of aura and its temporal relationship with the next evolving symptom during attack differentiate between subgroups of migraine [21]. Aura in migraine serves as a boundary between "migraine without aura" and "migraine with aura" [22] and "migraine-related condition.…”
Section: Clinical Characteristics Of Auramentioning
confidence: 99%